The e-consumer as part of a circular economy - Lorek, Paweł (E-konsument jako część gospodarki okrężnej, 2020)
The article is related to the problem of the transition of today’s economic system towards a circular economy model. This transformation is becoming a necessity due to environmental limitations. An interesting issue is the role of ICT in this matter, especially internet technologies. According to the presented analysis, these technologies do have capabilities to support consumer activities, which are consistent with the principles of a circular economy. This support can be essential for changing consumer’s attitudes and making their consumption patterns more sustainable. Nevertheless, there are some technical, social and economic barriers which may occur during this process. Literature analysis and critical analysis were used as research methods. The article concludes that, despite many barriers, the potential of internet technologies for circular economy support is very promising
Informatyka Ekonomiczna = Business Informatics, 2020, Nr 1 (55), s. 60-68
Keywords: circular economy; e-consumer; internet technologies; gospodarka okrężna; e-konsument; technologie internetowe